The effects of concrete-pictorial-abstract (CPA) teaching method on the Malaysian community college students’ attitude towards Geometry - Nur Alyani Mohamed,; Chew, Cheng Meng (Penerbit Universiti Kebangsaan Malaysia, 2021)
Community college is an institution that provides training and skills for post-secondary education leavers to become skilled workforce with minimum enrolment requirements. However, the admission of students who possessed low basic knowledge of Mathematics has somehow affected the Geometry teaching and learning process. These students show less interest and attitude in learning Mathematics. This quasi-experimental study aimed to investigate the effect of the CPA teaching method on Malaysian Community College students’ attitudes towards Geometry. A total of 60 students who registered their first semester Mathematics module from Pulau Pinang and Kedah Community Colleges was selected as samples. The control group used the conventional method (non-CPA), while the experimental group used concrete-pictorial-abstract (CPA) method. Questionnaires were used as the instrument. Data were analyzed using one-way ANCOVA. It was found that there are significant differences in attitude towards Geometry between the control and experimental group. This result provides positive effects on the implementation of CPA approach in the teaching and learning of Geometry. This study hence suggests that educators in Malaysia to integrate CPA teaching methods in their teaching and learning process of Geometry, which will have a better implication on the attitude of students studying Geometry.